2017
DOI: 10.5664/jcsm.6484
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sleep Duration with Sociodemographic Characteristics, Lifestyle, Mental Health, and Chronic Diseases in a Large Chinese Adult Population

Abstract: Study Objectives: Pattern of sleep duration and its correlates have rarely been reported in China. This study examined the sleep duration and its relationship with sociodemographic variables, lifestyle, mental health, and chronic diseases in a large Chinese adult population. Methods: This cross-sectional study used multistage stratified cluster sampling. A total of 17,320 participants from Jilin province were selected and interviewed using standardized assessment tools. Basic socio-demographic and clinical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 43 publications
4
66
5
3
Order By: Relevance
“…Our research detected the highest chance of short sleep in males, which is similar to the results of the NHANES 23 . However, other studies have found no difference by sex 8 , 9 . Individuals aged 40 to 59 years also had the highest chance of short sleep compared to younger ones.…”
Section: Discussionsupporting
confidence: 88%
“…Our research detected the highest chance of short sleep in males, which is similar to the results of the NHANES 23 . However, other studies have found no difference by sex 8 , 9 . Individuals aged 40 to 59 years also had the highest chance of short sleep compared to younger ones.…”
Section: Discussionsupporting
confidence: 88%
“…Epidemiological studies report consistent relationships between short sleep duration and increased risk for mortality, T2DM, hypertension, cardiovascular disease, stroke, coronary heart disease, overweight and obesity, weight gain, hyperglycaemia and impaired glucose tolerance (Anothaisintawee, Reutrakul, Van Cauter, & Thakkinstian, ; Bliwise, Greer, Scullin, & Phillips, ; Cappuccio et al., ; Chao et al., ; Gottlieb et al., , ; Itani, Jike, Watanabe, & Kaneita, ; Knutson et al., ; Patel & Hu, ; Roda et al., ; Sasaki et al., ; Sperry, Scully, Gramzow, & Jorgensen, ; Walatara, Athiththan, Hettiaratchi, & Perera, ; Wu, Zhai, & Zhang, ). Furthermore, poor lifestyle factors, such as smoking (Wang et al., ), lack of physical exercise (Wang et al., ) and alcohol use (Galli et al., ), are more common in short‐sleeping individuals, presumably compounding their risk for developing NCDs. Both short and long sleep have also been associated with depression (Zhai, Zhang, & Zhang, ), and depression severity has been associated with metabolic syndrome components (Hiles, Révész, Lamers, Giltay, & Penninx, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this meta‐analysis, the proportion of short sleep (<6 hours/day) in hospital was significantly higher than in the community. Hospitalized patients with diabetes are clinically unstable with physical comorbidities, which could lead to short sleep . In addition, the hospital environment may affect sleep; for example, around 39% of patients with diabetes complained that other patients or caregivers often disrupt their sleep .…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalized patients with diabetes are clinically unstable with physical comorbidities, which could lead to short sleep. 72 In addition, the hospital environment may affect sleep; for example, around 39% of patients with diabetes complained that other patients or caregivers often disrupt their sleep. 73 In this meta-analysis, short sleep was positively associated with a small sample size.…”
Section: Discussionmentioning
confidence: 99%